2019
DOI: 10.1111/evo.13852
|View full text |Cite
|
Sign up to set email alerts
|

Conflicting selection onCneorum tricoccon(Rutaceae) seed size caused by native and alien seed dispersers

Abstract: The disappearance of native seed dispersers due to anthropogenic activities is often accompanied by the introduction of alien species, which may to some extent replace the ecological service provided by the extinct ones. Yet, little empirical evidence exists demonstrating the evolutionary consequences of such alien “replacement.” Here, we document the conflicting selection exerted on seed size by two native lizards (Podarcis lilfordi and P. pityusensis) and an alien mammal species (Martes martes), all acting a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 73 publications
4
14
0
Order By: Relevance
“…Similar patterns are found in another kind of natural experiment, in a system in which native frugivorous lizards exert negative directional selection on seed diameter (i.e. selecting for smaller seeds), while invading martens exert positive directional selection, thus driving an increase in seed size (Traveset, Escribano‐Avila, Gómez, & Valido, 2019). This is possibly a unique demonstration of the substrate on which seed dispersal syndromes have evolved multiple times: disruptive selection on a filtering trait‐like size was followed by directional selection on other traits that match the relevant disperser.…”
Section: Evidence For Frugivore–fruit Coevolutionsupporting
confidence: 73%
“…Similar patterns are found in another kind of natural experiment, in a system in which native frugivorous lizards exert negative directional selection on seed diameter (i.e. selecting for smaller seeds), while invading martens exert positive directional selection, thus driving an increase in seed size (Traveset, Escribano‐Avila, Gómez, & Valido, 2019). This is possibly a unique demonstration of the substrate on which seed dispersal syndromes have evolved multiple times: disruptive selection on a filtering trait‐like size was followed by directional selection on other traits that match the relevant disperser.…”
Section: Evidence For Frugivore–fruit Coevolutionsupporting
confidence: 73%
“…Our study showed that fruit diameter correlated positively with the number or the mean mass of seeds in eight of the nine studied plant species. This suggests that a positive relationship between fruit diameter and seed traits is common in fleshyfruited plants, in line with the findings of many single-species studies (e.g., Herrera, 1988;Sallabanks, 1993;Herrera et al, 1994;Jordano, 1995b;Alcántara and Rey, 2003;Hernández, 2009;Rodríguez-Pérez and Traveset, 2010;González-Castro et al, 2019;Traveset et al, 2019;Carvalho et al, 2021). Potential mismatches between gapes and fruits can, therefore, decrease the mass and the number of dispersed seeds in small-gaped dispersers, as this was shown for four of the nine studied plant species.…”
Section: Discussionsupporting
confidence: 87%
“…The positive correlation between fruit size and seed size (Alcántara and Rey, 2003) also explains the smaller seeds dispersed by S. atricapilla than by large-gaped T. philomelos (González-Varo et al, 2014). For the spurge olive Cneuorum tricoccon, larger seeds were found in the scat of M. martes than in that of small-gaped lizards (Traveset et al, 2019). Even in aggregated fruits such as Rubus spp., avian frugivores may select for seeds of different sizes by selecting fruits of different sizes (e.g., Jordano, 1984b).…”
Section: Discussionmentioning
confidence: 95%
“…In addition, attacks on humans are possible, but rare, 13 when colonial nests are established in urban areas or when people get to close to the colonies without noting their presence in natural areas. In the particular case of Majorca, this invasion could be devastating, considering the situation of the populations of honeybees, the fragility of the ecosystem (typical of the island ecosystems) 14,15 and the impact on endemic insects 16 …”
Section: Introductionmentioning
confidence: 99%